THE INFLUENCE OF LIFE DOMAINS ON ADOLESCENT AND ADULT OFFENDING: TESTING AN EXTENSION OF AGNEW’S GENERAL THEORY - Calvert, Joseph Mark (2018)
More than a decade has passed since Agnew (2005) introduced his General Theory of Crime and Delinquency (GTCD). Despite this interval, GTCD remains a relatively untested theory. Drawing on previous testing efforts, the current research provides a systematic assessment of Agnew's theoretical propositions. It also provides only the second empirical examination of Cochran's (2015) extension of GTCD, which incorporates religion as a sixth distinct life domain. Nested negative binomial regression modeling and Poisson regression modeling are used to assess the effects of life domains on several diverse forms of self-reported criminal behavior at two distinct stages of development: adolescence and adulthood. Data are drawn from two waves of the second generation of the Kaplan Longitudinal and Multigenerational Study. Consistent with prior empirical tests, results provide mixed support for theoretical propositions, highlighting the complexity of Agnew’s initial theory. Specifically, general support is provided for the direct effects of both theories’ variables, indicating they are important to the explanation of crime. Also, in line with Cochran's findings, initial observed effects of religious variables on criminal behavior are reduced to non-significance when all other predictors are introduced in most regression models, hinting that the incorporation of such variables may be incongruous with Agnew's chosen method of theoretical integration. However, religious variables emerge as significant predictors of general crime during adulthood, suggesting that the relationship between these variables and crime is more complex than anticipated. Additionally, strong support is found for the proposition that the effects of life domains are primarily contemporaneous. Results offer weaker support, however, for the assertion that life domain effects are largely mediated by constraints against crime and motivations towards it. Policy implications for the creation of theoretically-informed crime prevention and intervention strategies tailored to specific developmental stage are discussed